Randai as Traditional Minangkabau Culture In Padang Pariaman: A Semiotic Analysis - Aditiawarman, Mac; Yulia, Yulia (Jurnal Ilmiah Langue and Parole, 2025)
This research discusses linguistics signs in randai art originating from west sumatera, randai is a traditional minangkabau drama or theater performance art which is rich in art, noble values and linguistic element in each element of randai, namely, music, drama, gurindam, galombng or dance and silek. Linguistics elements that have meaning in each element are visualized in legaran movements in the form of circular patterns which function as a form of change in time between one scene and the next scene. This research aims to analyze and describe the lingual signs and body language signs found in randai elements and function in the context of minangkabau culture.The research method used is descriptive qualitative, with data collected through field observations, interviews, documentation in the form of videos and photos with art pioneers, members of legaran randai. Then the researcher conducted a literature study using Saussure and Barthes semiotics theory. The results of this research show that randai is a complex performing art that combines elements of movement or silek, music, dialogue and singing. The randai movement has distinctive characteristics that reflect the noble values and philosophy of Minangkabau culture, namely leadership and mutual cooperation and a sense of unity. Randai also has a function as a medium for education, entertainment that conveys moral messages or social criticism as well as a form of local minangkabau wisdom.